2019
DOI: 10.1002/aelm.201900234
|View full text |Cite
|
Sign up to set email alerts
|

Design of Mixed‐Cation Tri‐Layered Pb‐Free Halide Perovskites for Optoelectronic Applications

Abstract: the recorded photovoltaic (PV) efficiency is over 23% in the laboratory. [1,[4][5][6] Such merits for high-performance optoelectronics are governed by their unique electronic structure features, which can mainly be attributed to the ns 2 lone-pair electrons of Pb 2+ and Sn 2+ cations. [7,8] The presence of ns 2 cations in these perovskites gives rise to pronounced curvature in both valence and conduction band edges through considerable antibonding hybridization with the halide anions. This facilitates the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…They successfully identified six orthorhombic lead‐free hybrid organic–inorganic perovskites with ideal bandgap (0.9–1.6 eV) and room temperature thermal stability from 5,158 unexplored hybrid organic–inorganic perovskites. Liu et al 188 identified a set of mixed‐cation tri‐layered Pb‐free halide perovskites (A 4 MM′ 2 X 12 ) with the HT material screening framework. First, they selected four ground state scaffold structure as the structure prototypes.…”
Section: Ht Computational Materials Screening and Discovery Of Optoelmentioning
confidence: 99%
“…They successfully identified six orthorhombic lead‐free hybrid organic–inorganic perovskites with ideal bandgap (0.9–1.6 eV) and room temperature thermal stability from 5,158 unexplored hybrid organic–inorganic perovskites. Liu et al 188 identified a set of mixed‐cation tri‐layered Pb‐free halide perovskites (A 4 MM′ 2 X 12 ) with the HT material screening framework. First, they selected four ground state scaffold structure as the structure prototypes.…”
Section: Ht Computational Materials Screening and Discovery Of Optoelmentioning
confidence: 99%
“…As shown in Figure a–c and Figure S4, Supporting Information, ground‐state Rb 4 SnSb 2 Br 12 may be stable in the region of −1.3 eV ≦ Δμ Sn ≦ −0.6 eV, which is consistent with a previous study (≈−1.4 eV to −0.5 eV). [ 35 ] Therefore, growing high quality Rb 4 SnSb 2 Br 12 thin film is expected to be challenging, similar to other quaternary compounds. [ 36–38 ] It is worth noting that density functional theory (DFT) calculations might underestimate the stability of some perovskite compounds.…”
Section: Resultsmentioning
confidence: 99%
“…They also found that thickness adjustment of the inserted layers can tune the compounds’ bandgaps and effective masses. Later in 2019, Liu et al studied A 4 MM' 2 X 12 compounds by computational screening of different element combinations, namely A = (K + and Cs + ), M = (Zn 2+ and Sn 2+ ), M' = (Bi 3+ and Sb 3+ ), and X = (Cl − , Br − , and I − ) 114 . The authors first determined the ground‐state scaffold structure of the compounds by comparing different crystal structures and M/M' configurations.…”
Section: Ht Materials Designmentioning
confidence: 99%
“…Later in 2019, Liu et al studied A 4 MM' 2 X 12 compounds by computational screening of different element combinations, namely A = (K + and Cs + ), M = (Zn 2+ and Sn 2+ ), M' = (Bi 3+ and Sb 3+ ), and X = (Cl − , Br − , and I − ). 114 The authors first determined the ground-state scaffold structure of the compounds by comparing different crystal structures and M/M' configurations. Second, they checked decomposition pathways and phase diagrams to screen the thermodynamic stability.…”
Section: Perovskite Derivativesmentioning
confidence: 99%